Opportunities and Challenges in Development Community-Based Marine Ecotourism on Samalona Island, Makassar City - Yudha Prakasa; Sawu, Michael Rudolfus; Ulinnuha, Muhammad Farid (Journal of Tourism Sustainability, 2023)
This study aims to assess the potential of developing community-based marine ecotourism on Samalona Island. The research seeks to analyze the policies concerning marine ecotourism development, the level of community engagement in this process, and the social consequences of implementing community-based marine ecotourism on Samalona Island, Makassar City. The study employs a verification approach within qualitative research, where the researchers act as instruments in data collection through various methods such as observation, interviews, documentation, and literature review. The findings of this study reveal several significant points. Firstly, the inadequacy of the community-based ecotourism development policy targeting Samalona Island is evident, partly attributed to the lack of a comprehensive Makassar City tourism development master plan. Additionally, the level of community participation in the planning and development of the tourism sector is limited, primarily confined to endorsing policies without actively contributing to decision-making processes. Despite its ability to boost the local economy, the positive environmental impact of community-based marine ecotourism on Samalona Island remains minimal. However, the study recognizes that this article contributes to a better understanding of the potential for marine ecotourism development on Samalona Island.